The History Highway - A 21st Century Guide To Internet Resources - Hoikkala, Paivi (Teaching History: A Journal of Methods, 2007)
The Internet represents an astounding historical transformation in the acquisition of knowledge and exchange of information. According to the Central Intelligence Agency, there were over one million Internet users in the world in 2005, over twenty percent of them in the United States alone. The number of Web pages is growing so fast that it is impossible to give any reliable figures; the best estimates suggest more than eight million. lt is impossible for educators to ignore these developments; instead, we are better off to embrace the resources available. To help us make sense of the dizzying maze of the Internet comes The History Highway.